2020
DOI: 10.3390/mi12010007
|View full text |Cite
|
Sign up to set email alerts
|

Large-Signal Linearity and High-Frequency Noise of Passivated AlGaN/GaN High-Electron Mobility Transistors

Abstract: This study proposes AlGaN/GaN/silicon high-electron mobility transistors (HEMTs) grown by a metallorganic chemical vapor deposition (MOCVD) system. The large-signal linearity and high-frequency noise of HEMTs without and with different passivation layers are compared. The experimental data show that the addition of a TiO2 passivation layer to undoped AlGaN/GaN HEMT’s increases the value of the third-order intercept point (OIP3) by up to 70% at 2.4 GHz. Furthermore, the minimum noise figure (NFmin) of the HEMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…GaN has the favorable properties of a big bandgap, an enhanced breakdown electric field, and high thermal conductivity. AlGaN/GaN is a key material system in fifth generation (5G) applications in the field of microwave communication [ 1 , 2 , 3 , 4 ]. An AlGaN/GaN heterostructure generates a high two-dimensional electron gas (2-DEG) by spontaneous and piezoelectric polarization effects [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…GaN has the favorable properties of a big bandgap, an enhanced breakdown electric field, and high thermal conductivity. AlGaN/GaN is a key material system in fifth generation (5G) applications in the field of microwave communication [ 1 , 2 , 3 , 4 ]. An AlGaN/GaN heterostructure generates a high two-dimensional electron gas (2-DEG) by spontaneous and piezoelectric polarization effects [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…As compared to the GaN channel device, the InGaN channel device exhibited better noise performance as it owns a higher electron drift velocity. The effect of passivation on the device noise performance was investigated in [10]. It was observed that the passivation improves the noise performance of the GaN HEMT.…”
Section: Introductionmentioning
confidence: 99%